Development and application of edible coatings in minimally processed fruit - ANDRADE PIZARRO, Ricardo D.; PÉREZ CERVERA, Carmen E.; LUJÁN RHENALS, Deivis E. (Vitae, 2016)
The consumer’s interest to purchase safe, nutritious, minimally processed, and healthy food has increased consumption of various fruits and vegetables. Generally, the quality of fruits depends on nutritional, microbiological and organoleptic properties, all of which are exposed to dynamic changes during harvesting, storage, and marketing. These changes are mainly due to the interactions between the fruits and its surroundings or migration among different inner components, which can result in loss of moisture and some volatile compounds.